Interactions Between Atopic Dermatitis and Staphylococcus aureus Infection: Clinical Implications - Kim, Jihyun; Kim, Byung Eui; Ahn, Kangmo; Leung, Donald Y. M. (Allergy, asthma & immunology research, 2019)
commonly colonizes the skin of atopic dermatitis (AD) patients and contributes to the development and exacerbation of AD. Multiple factors are associated with colonization of AD skin by , including the strength of -corneocyte adhesion, deficiency of antimicrobial peptides, decreased levels of filaggrin and filaggrin degradation products, overexpressed Th2/Th17 cytokines, microbial dysbiosis and altered lipid profiles. colonization on AD skin causes skin barrier dysfunction through virulence factors such as superantigens (toxins), enzymes and other proteins. Furthermore, colonization of AD skin by exacerbates AD and may contribute to microbial dysbiosis, allergen sensitization, Th2/Th17 polarization, development of atopic march and food allergy in AD patients. Skin colonization of , particularly methicillin-resistant (MRSA), is one of the major challenges commonly encountered in the management of AD. Bleach bath, and topical or systemic antibiotics could be used to control infection on AD skin. However, careful use of antibiotics is required to control the occurence of MRSA. Recently, various strategies, including microbiome transplant, monoclonal antibodies against virulent toxins, vaccines and recombinant phage endolysin, have been studied to control infection on AD skin. Further advances in our understanding of could provide us with ways to manage colonization more effectively in AD patients.